Penerapan Ideologi dan Konstitusi Negara Indonesia Dewasa Ini - Juremi, Radi Anky (Pelita Harapan University, 2006)
Ideology and Constitution are fundamentally needed for a sovereign states such as Indonesian Republic. It is because ideology will give shapes of any regulations that exist in a state constitution, and those constitutions will give a role model of the implementation in establishing a state, because of that the existence of ideology and a sovereign constitution for a state is crucial in initiating the state objective. Pancasila and The 1945 Constitution to Indonesian Republic are a basic guidelines to reach the objective. But nowadays in the process of Indonesia reformation where the center attention are Â in reform of the political system, the 1945 Constitution has been amendment, so it seems by public view Pancasila as our state Ideology has been submerged. Does the amendment of the 1945 constitution really discard Pancasila as our Ideology ? and how the implementation of the amendment of the 1945 constitution ?